Selection of imprinted nanoparticles by affinity chromatography - Guerreiro, Antonio R.; Chianella, Iva; Piletska, Elena V.; Whitcombe, Michael J.; Piletsky, Sergey A. (Elsevier Science B.V., Amsterdam., 2009)
Soluble molecularly imprinted nanoparticles were synthesised via iniferter initiated polymerisation and separated by size via gel permeation chromatography. Subsequent fractionation of these particles by affinity chromatography allowed the separation of high affinity fractions from the mixture of nanoparticles. Fractions selected this way possess affinity similar to that of natural antibodies (Kd 6.6 × 10−8) M and were also able to discriminate between related functional analogues of the template.
Keywords: Molecularly imprinted polymer; Nanoparticle; Affinity chromatography